Signal-Based Self-Organization of a Chain of UAVs for Subterranean Exploration - Laclau, Pierre; Tempez, Vladislav; Ruffier, Franck; Natalizio, Enrico; Mouret, Jean-Baptiste (Frontiers in Robotics and AI, 2021)
Miniature multi-rotors are promising robots for navigating subterranean networks, but maintaining a radio connection underground is challenging. In this paper, we introduce a distributed algorithm, called U-Chain (for Underground-chain), that coordinates a chain of flying robots between an exploration drone and an operator. Our algorithm only uses the measurement of the signal quality between two successive robots and an estimate of the ground speed based on an optic flow sensor. It leverages a distributed policy for each UAV and a Kalman filter to get reliable estimates of the signal quality. We evaluate our approach formally and in simulation, and we describe experimental results with a chain of 3 real miniature quadrotors (12 by 12 cm) and a base station.